2014
DOI: 10.1371/journal.pone.0106219
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-Like Oxidized LDL Receptor-1 Is an Enhancer of Tumor Angiogenesis in Human Prostate Cancer Cells

Abstract: Altered expression and function of lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) has been associated with several diseases such as endothelial dysfunction, atherosclerosis and obesity. In these pathologies, oxLDL/LOX-1 activates signaling pathways that promote cell proliferation, cell motility and angiogenesis. Recent studies have indicated that olr1 mRNA is over-expressed in stage III and IV of human prostatic adenocarcinomas. However, the function of LOX-1 in prostate cancer angiogenesis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…Taken together, the results indicate that LOX-1 promotes the invasion and migration of GC cells via PI3K/Akt/GSK3β-mediated EMT. Additionally, by binding to ox-LDL, LOX-1 could increase the expression of several proangiogenic factors such as vascular endothelial growth factor and matrix metalloprotease343536, which could contribute to tumor growth, invasion and metastasis3738. These findings indicate another mechanism that LOX-1 may also enhance tumor angiogenesis to facilitate cancer metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, the results indicate that LOX-1 promotes the invasion and migration of GC cells via PI3K/Akt/GSK3β-mediated EMT. Additionally, by binding to ox-LDL, LOX-1 could increase the expression of several proangiogenic factors such as vascular endothelial growth factor and matrix metalloprotease343536, which could contribute to tumor growth, invasion and metastasis3738. These findings indicate another mechanism that LOX-1 may also enhance tumor angiogenesis to facilitate cancer metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, a high expression of LOX-1 is correlated with a worse prognosis in patients suffering from gastric (69), colorectal (70), or prostate (71) cancer. Functionally, the triggering of LOX-1 by oxLDL was shown to induce TNF-α expression, tumor angiogenesis and tumor cell trans-endothelial migration and metastasis in prostate or breast cancers (71,72). Interestingly, a high expression of LOX-1 was reported on polymorphonuclear myeloid-derived suppressor cells from peripheral blood and tumor of cancer patients (up to 5-50%), whereas its expression is almost undetectable on blood neutrophils from healthy donors (73).…”
Section: Clec8a (Lox-1 Olr-1)mentioning
confidence: 99%
“…Increased expression of LOX‐1 has been seen in human prostate adenocarcinomas at stages III and IV which require new vascularization and angiogenesis for local invasion . It has also been suggested that LOX‐1 is an essential regulator in prostate cancer cells, with the ability to enhance tumor angiogenesis toward malignancy and metastasis in obese patients . In a recent work, it was suggested that LOX‐1 is a novel biomarker and molecular target for colorectal cancer.…”
Section: Lox‐1 and Disease Stressmentioning
confidence: 99%